Arah dan Perubahan Kebijakan Seleksi Mandiri Calon Mahasiswa Program Sarjana - Khalilah Khalilah (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
Changes in the student admission through an independent selection path have been conducted by Indonesian government/Ministry of education, culture, research and technology. Recently, the undergraduate student admission through an independent selection path was amended when Rector of State University of Lampung (UNILA) was detained by Indonesian Corupsion Commission through catch hands operation or OTT. A specific research focusing on such changes has been under-developed however. This article is specified to discuss this issue. Regulation documents related with this issue published by this government/ministry were exctracted using thematic qualitative content analysis. The findings are as follows. Changes in the undergraduate student admission policy have been formulated by this government/ministry since Law No.12/2012 was enacted up to 2022s. Commercial oriented undergraduate student admissions was explicitly prohibited by this law. However, regulations constituted by this government/ministry in between 2015s and 2020s did not restrain this issue straightforwardly. As such OTT incident took place, this ministry decreed a regulation, named as Permenristikdikti No.48/2022. Commercial-oriented undergraduate student admission using independent selection path was strictly prohibited by this regulation. This principle does not constrain Indonesian state universities’ authonomy regarding the undergraduate student admision. It instead, helps them to not being trapped in corruptive circle behaviors.